GAMBARAN PROFIL LIPID PADA SISWA OBESE DI SMP NEGERI 1 MANADO - Iksan, Astrid Noviera; Manampiring, Aaltje; ., Fatimawali (Universitas Sam Ratulangi, 2015)
Abstract: Obesity is an abnormal condition of fat accumulation that can disrupt our health. Obesity problem experienced by some groups of people, one of them is teenager. Blood lipid profile level in obesity children is similar to lipid profile in cardiovascular disease and obesity children also had higher risk of hypertension. Lipid profile is a condition of blood lipid observed by cholesterol total such as LDL, HDL and triglyceride. According to International Diabetes Federation (IDF) criteria, obesity categorized if waist circumference ?90 cm for male and ?80 for female. The objective is to determine overview of lipid profile in obese student of SMP Negeri 1 Manado. The research used observational method with cross sectional study, which obesity measured by waist circumference and laboratory results of blood lipid profile level.Based on the waist circumference in 371 populations, there were 97 students included to obesity category and by 97 students, only 13 obesity students took part in the research. There were 2 (15,3%) students had total cholesterol level above normal, 3 (23,1%) students had LDL level above normal, 1 (7,7%) student had HDL level below normal and 2 (15,4%) students hadtriglyceride level above normal.Keywords: obesity, student, adolescents, lipid profile, SMP Negeri 1 ManadoAbstrak: Obesitas merupakan keadaan abnormal penumpukan lemak yang dapat mengganggu kesehatan. Masalah obesitas banyak dialami oleh beberapa golongan masyarakat salah satunya remaja. Kadar profil lipid darah pada anak obesitas menyerupai profil lipid pada penyakit kardiovaskular dan anak yang obesitas mempunyai risiko hipertensi lebih besar. Profil lipid adalah keadaan lemak darah yang ditinjau dari kandungan total kolestrol dalam darah, LDL, HDL dan Trigliserida. Sesuai kriteria International Diabetes federation (IDF) dikategorikan obesitas jika nilai lingkar pinggang ?90 cm untuk laki-laki dan ?80 cm pada perempuan. Penelitian ini bertujuan untuk mengetahui gambaran profil lipid pada siswa obesitas di SMP Negeri 1 Manado.Penelitian dilakukan menggunakan metode observasional dengan desain crosssectional study, dimana obesitas diukur berdasarkan lingkar pinggang dan kadar profil lipid di periksa di laboratorium. Berdasarkan hasil pemeriksaan lingkar pinggang pada 371 populasi didapatkan 97 siswa termasuk dalam kategori obesitas dan dari 97 siswa tersebut hanya 13 siswa yang bersedia untuk melakukan pemeriksaan profil lipid. Dari hasil pemeriksaan tersebut didapatkan 2 (15.3%) siswa obesitas memiliki kadar kolestrol total diatas normal, 3 (23.1%) siswa obesitas memiliki kadar LDL diatas normal, 1 (7.7%) siswa obesitas memiliki kadar HDL dibawah normal, dan 2 (15.4%) siswa obesitas memiliki kadar Trigliserida diatas normal. KataKunci : obesitas, siswa, remaja, profil lipid, SMP Negeri 1 Manado